The Effect of Breastcare on the Smoothness of Breast Milk in Postpartum Mothers - Fiyola Ladyvia (JURNAL KEBIDANAN KESTRA (JKK), 2025)
Breast Care is one method that can be used to overcome problems in the breastfeeding process, especially during the postpartum period, so that the process of releasing breast milk can run smoothly. Side effects that arise due to the use of drugs containing chemicals, a simple and efficient care solution is needed. Health services highlight the importance of providing quality and effective care, which can also be done independently. This study applies a pre-experimental design with a one-group pretest-posttest design approach. The study was conducted at PMB E in January 2025, involving 15 breastfeeding postpartum mothers selected using the total sampling method. Measurement of pain levels was carried out using the Numeric Rating Scale (NRS), while breast engorgement was assessed using the Six Point Engorgement Scale (SPES), both before and after the intervention was given. The results of this study indicate that breastcare interventions are effective in reducing breast engorgement and pain intensity in postpartum mothers. The average breast engorgement decreased from 2.46 to 1.32 after the intervention, with a decrease of 1.14. Meanwhile, the average pain intensity decreased from 3.88 to 2.34 after the intervention, with a decrease of 1.54. The results of the Wilcoxon statistical test showed that there was a significant effect of breast care on the smoothness of breast milk in postpartum mothers, with a p value = 0.000 (? <0.05). Therefore, breast care can be used as an effective alternative therapy to increase the smoothness of breast milk in postpartum mothers.